A Survey of Self-Interference Management Techniques for Single Frequency Full Duplex Systems - Chinaemerem David Nwankwo; Lei Zhang; Atta Quddus; Muhammad Ali Imran; Rahim Tafazolli (IEEE Access, 2018)
This paper presents a comprehensive survey of the literature on self-interference management schemes required to achieve a single frequency full duplex (FD) communication in wireless communication networks. A single frequency FD system often referred to as in-band FD system has emerged as an interesting solution for the next generation mobile networks, where the scarcity of available radio spectrum is an important issue. Although studies on the mitigation of self-interference have been documented in the literature, this is the first holistic attempt at presenting not just the various techniques available for handling self-interference that arises when an FD device is enabled, as a survey, but it also discusses other system impairments that significantly affect the self-interference management of the system, and not only in terrestrial systems, but also on satellite communication systems. The survey provides a taxonomy of selfinterference management schemes and shows by means of comparisons the strengths and limitations of various self-interference management schemes. It also quantifies the amount of self-interference cancellation required for different access schemes from the first generation to the candidate fifth generation of mobile cellular systems. Importantly, the survey summarizes the lessons learnt, identifies and presents open research questions and key research areas for the future. This paper is intended to be a guide and take off point for further work on self-interference management in order to achieve FD transmission in mobile networks, including heterogeneous cellular networks, which is undeniably the network of the future wireless systems.